Compliance with Fluoride Supplements Provided by a Dental Hygienist in Homes of Low-Income Parents of Preschool Children in Quebec - Fabien Gagnon, MD, MSc; Pierre Catellier, DMD; Isabelle Arteau-Gauthier; (Blackwell Synergy, 2007)
This study aimed to assess the compliance with fluoride supplements provided at home by a dental hygienist to mothers of at-risk preschool children.